Corporate litigation and changes in CEO reputation: Guidance from U.S. Federal Court lawsuits. Issue 1 (April 2016) - Liu, Chelsea; Aharony, Joseph; Richardson, Grant; Yawson, Alfred
Abstract: This study examines corporate litigation and changes in CEO reputation. Based on a sample of 9959 filed and settled environmental, antitrust, intellectual property (IP) and contractual lawsuits in the U.S. Federal Courts over the 2000–2007 period, we find that CEOs experience poorer reemployment prospects following contractual lawsuits. Additionally, reputational consequences depend significantly on the nature of the allegation and lawsuit merit. We also observe that IP lawsuits are associated with an increase in the number of outside board seats; no penalties follow politically sensitive environmental lawsuits. Overall, our findings contribute to the extant literature on market-based penalties for corporate wrongdoing.